Population and Vital Statistics Report 2024 - United Nations Department of Economic; Social Affairs (United Nations, 2024)
The Population and Vital Statistics Report presents data for countries or areas on population size (total, male, and female) from the latest available census, estimated total population size for the latest available year, and the number and rate of vital events (live births, deaths, and infant deaths) for the latest available year within the past 15 years. These data are presented as reported by national statistical authorities to the Demographic Yearbook of the Statistics Division of the United Nations Department of Economic and Social Affairs.